Comparative survival efficacy of mechanical and biological heart valve in dialysis patients: a meta-analysis with the subgroup analysis of valve positions. (25th November 2020) - Chi, K.Y; Chiang, M.H; Kang, Y.N; Wang, S.T; Li, S.J; Chan, Y.T; Chen, Y.C; Chen, W.C
Abstract: Background: To date, the optimal selection of prosthetic heart valve for dialysis patients still remains controversial. Purpose: Since previous meta-analyses on survival outcomes were with substantial heterogeneity, we attempted to investigate the potential sources and update the comparative survival efficacy of mechanical prosthesis (MP) and bioprosthesis (BP) in dialysis patients. Methods: We systematically reviewed PubMed, Embase, Cochrane library, Web of Science, and ClinicalTrials.gov from inception to February 1, 2020 for relevant studies. Randomized controlled trials, prospective or retrospective cohorts that involved dialysis patients undergoing heart valve replacement were included. Studies that did not report comparative survival outcome of two prostheses were excluded. To explore the potential sources of heterogeneity, we conducted a subgroup analysis based on valve positions. We also performed a meta-regression to delve into the effects of study-level covariates on mid/long-term survival, which was defined as at least 4-year follow-up. Results: A total of 20 retrospective cohorts involving 8, 398 participants (MP= 5900, BP= 2498) were included in our study. Overall, MP was associated with a significant 16% reduction in all-cause mortality, compared to BP (HR, 0.84; 95% CI, 0.73 to 0.98; I 2 =43%; Figure). In the subgroup analysis, patients undergoing isolated-aortic valve replacement (iso-AVR) with MP further exhibited an even better mid/long-term survival efficacy with no statistical heterogeneity being observed (HR, 0.64; 95% CI, 0.47 to 0.86; I 2 = 0%; Figure). The involvement of mitral valve replacement (MVR) was a strong mortality contributor (HR, 1.79; 95% CI, 1.40 to 2.28; I 2 = 0%). Moreover, our meta-regression demonstrated that MVR proportion was the only covariate that significantly affected mid/long-term survival (β= 0.8473, p=0.046; Table). Conclusions: Compared to BP, MP might be a reasonable choice for dialysis patients requiring AVR due to its better mid/long-term survival efficacy. Funding Acknowledgement: Type of funding source: None